THE ROLE OF INNOVATIONS IN PROVIDING FINANCE SECURITY OF COMPANIES - Elena I. Gromova (Plekhanov Russian University of Economics, 2017)
The article investigates trends and problems of strategic management of companies in order to provide their finance security. Designing and implementing innovation strategy as an important element of strategic management, which includes designing and introduction of technological, marketing and organizational innovations is a top-priority objective of Russian companies in the current situation of economic and political risks. Analysis of the present day condition of innovation activity showed its very low level. The author puts forward a new approach to speeding up innovation development of Russian companies through developing a system of encouraging their managerial bodies to introduction of innovation. A set of indicators showing the extent and volume of innovation activity was built.